The Influence of Perceived Value on Purchase Decision Mediated by Brand Image in Garuda Indonesia Airline - Priscillia, Amanda sona; Yauwry, Andhika; Rendi Santo, So; Imanuella Dara, Pricilia; Ang, Angel (Jurnal Ecoment Global, 2025)
Objective: This study aims to examine the influence of perceived value on consumer purchase decisions, with brand image acting as a mediating variable, in the context of Garuda Indonesia Airlines. The objective is to provide empirical evidence that contributes to both theoretical understanding and practical strategy development in the airline service sector. Design/Methods/Approach: The study adopts a quantitative approach with an associative method. Data were collected through a survey of 61 Garuda Indonesia passengers aged over 18 who had flown with the airline more than twice. The sampling technique employed was saturated sampling. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software to evaluate both the measurement and structural models. Findings: The results show that perceived value has a positive and significant effect on both brand image and purchase decision. Additionally, brand image positively influences purchase decision and plays a mediating role in the relationship between perceived value and consumer decision-making. The analysis confirms that perceived value contributes not only directly to consumer behavior but also indirectly by shaping a strong brand image that reinforces purchasing intentions. Originality/Value: This study offers a novel integrative model by simultaneously examining perceived value, brand image, and purchase decision within the airline industry, particularly for a national carrier. It fills a gap in existing literature by exploring the mediating effect of brand image in a service context where intangible value perceptions significantly influence consumer choices. Practical/Policy implication: The findings suggest that airline companies should focus on enhancing perceived value through improved service quality, customer experience, and fair pricing. Simultaneously, reinforcing a strong and consistent brand image is essential to strengthen customer trust and loyalty, ultimately influencing purchase behavior and sustaining competitive advantage.